If a + b + c = 1 , a 2 + b 2 + c 2 = 2 , and a 3 + b 3 + c 3 = 3 , what is a 5 + b 5 + c 5 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same way!!!
To begin with, let's write down the equations:
a + b + c = 1 ••• 1
a 2 + b 2 + c 2 = 2 ••• 2
a 3 + b 3 + c 3 = 3 ••• 3
Let's approach the problem by trying to reach a 5 + b 5 + c 5 by expanding the multiplication of the 2 n d and 3 r d equations, grouping the terms, substituting values from the 1 s t equation, and distributing:
( a 2 + b 2 + c 2 ) ( a 3 + b 3 + c 3 )
= a 5 + a 2 b 3 + a 2 c 3 + a 3 b 2 + b 5 + b 2 c 3 + a 2 c 3 + b 3 c 2 + c 5
= a 5 + b 5 + c 5 + a 2 b 2 ( a + b ) + b 2 c 2 ( b + c ) + a 2 b 2 ( a + c )
= a 5 + b 5 + c 5 + a 2 b 2 ( 1 − c ) + b 2 c 2 ( 1 − a ) + a 2 b 2 ( 1 − b )
= a 5 + b 5 + c 5 + a 2 b 2 + b 2 c 2 + a 2 c 2 − a b c ( a b + b c + a c ) = 6
In an attempt to produce a b + b c + a c , let’s square the 1 s t equation, expand and factor:
( a + b + c ) 2 = 1 2
a 2 + b 2 + c 2 + 2 ( a b + b c + a c ) = 1
Let’s substitute the 2 n d equation and solve for a b + b c + a c :
2 + 2 ( a b + b c + a c ) = 1
Subtract 2 from both sides:
2 ( a b + b c + a c ) = − 1
Divide both sides by 2 :
a b + b c + a c = − 2 1
To produce a b c , let’s raise the 1 s t equation to the 3 r d power, expand, and factor:
( a + b + c ) 3 = 1 3
a 3 + b 3 + c 3 + 3 ( a 2 ( b + c ) + b 2 ( a + c ) + c 2 ( a + b ) ) + 6 a b c = 1
Let’s use the 1 s t equation to substitute values:
a 3 + b 3 + c 3 + 3 ( a 2 ( 1 − a ) + b 2 ( 1 − b ) + c 2 ( 1 − c ) ) + 6 a b c = 1
Let’s distribute:
a 3 + b 3 + c 3 + 3 ( a 2 + b 2 + c 2 − ( a 3 + b 3 + c 3 ) + 6 a b c = 1
Let’s substitute the 3 r d equation in:
3 + 3 ( a 2 + b 2 + c 2 − ( 3 ) ) + 6 a b c = 1
Let’s substitute the 2 n d equation:
3 + 3 ( ( 2 ) − ( 3 ) ) + 6 a b c = 1
After simplifying,
6 a b c = 1
Dividing both sides by 6 ,
We get a b c = 6 1 .
Let’s produce a 2 b 2 + b 2 c 2 + a 2 c 2 by squaring this equation we solved earlier, a b + b c + a c = − 2 1 :
( a b + b c + a c ) 2 = ( − 2 1 ) 2
Expanding and factoring,
a 2 b 2 + b 2 c 2 + a 2 c 2 + 2 a b c ( b + a + c ) = 4 1 .
Substituting a b c = 6 1 and the 1 s t equation,
a 2 b 2 + b 2 c 2 + a 2 c 2 + 2 ( 6 1 ) ( 1 ) = 4 1 .
Simplifying,
a 2 b 2 + b 2 c 2 + a 2 c 2 + 3 1 = 4 1 .
Subtracting 3 1 from both sides,
a 2 b 2 + b 2 c 2 + a 2 c 2 = 4 1 − 3 1 .
Simplifying,
a 2 b 2 + b 2 c 2 + a 2 c 2 = − 1 2 1 .
Substituting the boxed equations for their respective left-hand sides that are in the equation a 5 + b 5 + c 5 + a 2 b 2 + b 2 c 2 + a 2 c 2 − a b c ( a b + b c + a c ) = 6 ,
a 5 + b 5 + c 5 + ( − 1 2 1 ) − 6 1 ( − 2 1 ) = 6 .
Simplifying, a 5 + b 5 + c 5 = 6 .
The quantities a, b, c are the roots of the equation x 3 - x 2 - 2 x - 6 1 =0. Multiplying by x we get a 4 + b 4 + c 4 =coefficient of x in the equation x 4 - x 3 - 2 1 x 2 - 6 x =0, which is 6 2 5 . Repeating this process once again, we get a 5 + b 5 + c 5 =6
can u try this?
https://brilliant.org/problems/prove-this-looks-easy-huh/
Problem Loading...
Note Loading...
Set Loading...
Let P n = a n + b n + c n , where n is a positive integer; and S 1 = a + b + c , S 2 = a b + b c + c a , and S 3 = a b c . Using Newton's sum or Newton's identities as follows:
P 1 P 2 P 3 P 4 P 5 = S 1 = a + b + c = 1 = S 1 P 1 − 2 S 2 = ( 1 ) ( 1 ) − 2 S 2 = 2 = S 1 P 2 − S 2 P 1 + 3 S 3 = ( 1 ) ( 2 ) + 2 1 ( 1 ) + 3 S 3 = 3 = S 1 P 3 − S 2 P 2 + S 3 P 1 = ( 1 ) ( 3 ) + 2 1 ( 2 ) + 6 1 ( 1 ) = 6 2 5 = S 1 P 4 − S 2 P 3 + S 3 P 2 = ( 1 ) ( 6 2 5 ) + 2 1 ( 3 ) + 6 1 ( 2 ) = 6 ⟹ S 2 = − 2 1 ⟹ S 3 = − 6 1